THE EFFECTS OF TEACHING METACOGNITIVE STRATEGY TOWARDS READING COMPREHENSION ACHIEVEMENT BY THE SECOND YEAR STUDENTS OF SMA NEGERI 12 PEKANBARU - Doris Sukma Sukma; Eliwarti '; Nababan ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This experimental research aimed to measure how significant the effects of teaching metacognitive strategy in comprehending reading texts and the correlation between the variables. The sample of this research was the second year students of SMA Negeri 12 Pekanbaru. The participants were 35 students. The Null hypothesis was: There is no significant effect of teaching metacognitive strategy towards students reading comprehension achievement. The Alternative hypothesis was: There is a significant effect of teaching metacognitive strategy toward students reading comprehension achievement. The data were collected by means of reading comprehension test. The reliability of the test was 0.68 (high). The research finding revealed that: (a) the mean score of post-test (84.9) was higher than the mean score of pre-test (72.2) after the treatment. It means there was an enhancement to the mean score of the students. (b) after being calculated, it was found that the standard deviation and standard error for pre-test respectively were 9.41 and 1.56 while for post-test were 7.11 and 1.21. (c) the correlation (rxy) between the variables was 0.971 (very strong). (d) the value of “t” observed was 26.38. The degree of freedom (df) was 34. The value of df in 34 were 2.03 (the level of significance 5%) and 2.72 (the level of significance 1%). According to data analysis of this research, it can be concluded that there is a significant effect of teaching metacognitive strategy towards reading comprehension achievement by the second year students of SMA Negeri 12 pekanbaru.Keywords: Metacognitive Strategy, Teaching Metacognition, Reading Comprehension Achievement.